Impact of race and ethnicity on outcomes and health care utilization after allogeneic hematopoietic cell transplantation. Issue 4 (April 2015) - Khera, Nandita; Chang, Yu-Hui; Slack, James; Fauble, Veena; Leis, Jose F.; Noel, Pierre; Sproat, Lisa; Palmer, Jeanne; Adams, Roberta; Fitch, Tom; Northfelt, Donald; Guy, Mignonne; et al.
Abstract Disparities in outcomes after hematopoietic cell transplant (HCT) are reported mostly by registry studies. We examined the association of self-reported race and ethnicity with outcomes and health care utilization after allogeneic HCT in a single center study. Clinical and socioeconomic data of 296 adult patients who underwent allogeneic HCT from November 2003 to October 2012 were analyzed. Survival was compared between non-Hispanic Whites (NHW) and minority patients using Cox proportional hazards regression. Some 73% of patients were NHW and 27% were racial/ethnic minority patients. More minority patients were younger and had lower socioeconomic status. Both unadjusted and adjusted overall and progression-free survival were comparable between the two groups. High risk disease, poor performance score and Medicare/Tricare were significant predictors of mortality. Health care utilization was comparable between the two groups. Homogeneity of medical care for allogeneic HCT may help overcome racial/ethnic disparities, but not those due to patients' primary insurance.